Analysis of the efficiency of cash flow management using the example of the group of JSC «Kazakhtelecom» - Syzdykova, E.Zh.; Shakirova, G.A.; Shakirova , G.A. (BUKETOV BUSINESS REVIEW, 2018)
The article considers the analysis of the cash flow management efficiency on the example of the JSC «Kazakhtelecom» group. At the present stage, the implementation of the activity of any enterprise is possible only with the availability of funds and their rational use. The article provides an overview of the historical formation of such reporting format as cash flow statement. The authors give the main definitions reflecting the essence and characteristics of this report. The main objective that faces the management of cash flows in the enterprise is to determine the optimal size for the cash balance that is necessary to fulfill urgent financial obligations and to form investment opportunities for organizing short-term financial investments. In the article, the authors presented a detailed analysis of the inflow and outflow of cash, the structure of cash flows by type of activity. The authors present calculations on the coefficients of cash flow efficiency and illustrate the dynamics of changes in cash flows for the period of study. The article also presents the results of calculations of cash flow liquidity indicators for five years. The authors show that the management of cash flows acts as one of the most important financial levers that ensures the acceleration of the company’s capital turnover. Effective management of cash flows makes it possible to reduce the duration of the production and financial cycle, as well as reduce the need for capital, which is directed to servicing the economic activities of the enterprise.